The Role of PAM4 in the Management of Pancreatic Cancer: Diagnosis, Radioimmunodetection, and Radioimmunotherapy - Suxia Han; Guihua Jin; Lijuan Wang; Meng Li; Chenchen He; Xijing Guo; Qing Zhu (Journal of Immunology Research)
PAM4, a new monoclonal antibody (MAb) known as clivatuzumab, is highly reactive with pancreatic cancer and precursor lesions. It is absent from the normal tissues and has limited reactivity with nonpancreatic cancer. The detailed characteristic of the PAM4 epitope is unknown but recent studies have shown that it is dependent on MUC1 glycosylation status. The limited PAM4 expression pattern makes it an attractive candidate for management of pancreatic adenocarcinoma. In addition, PAM4 is a serum biomarker for diagnosis of pancreatic cancer. Several different radiolabeled immunodiagnostic and immunotherapeutic agents of PAM4 have been developed and some are being evaluated in preclinical and/or clinical studies. The review will focus on PAM4 and its potential utility for the diagnosis, radioimmunodetection, and radioimmunotherapy of pancreatic cancer.